ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKPAN MANAJEMEN RISIKO PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Atmi, Dian Renita; Damayanti (JURNAL EKONOMI, 2022)
This study was conducted to prove the effect of firm size, leverage, board size, board of commissioners gender diversity, and auditor reputation on risk management disclosure in banking companies listed on the Indonesia Stock Exchange. The object in this study is a banking company listed on the Indonesia Stock Exchange in 2015-2019. The type of data used is secondary data from the annual reports of banking companies obtained from the website www.idx.co.id. The sampling technique used is purposive sampling. The number of samples used in this study are 20 banking companies that consistently publish annual reports on the Indonesia Stock Exchange in 2015-2019 with a total of 100 observations. The data analysis technique used is logistic regression analysis. The results show that company size, board of commissioners size, and board of commissioners gender diversity have an insignificant negative effect on risk management disclosure, leverage and auditor reputation have a significant positive effect on risk management disclosure. The results of the coefficient of determination show a value of 0.254, which means that company size, leverage, board of commissioners size, gender diversity of the board of commissioners, and auditor reputation are able to explain risk management disclosure by 25.4% while theremaining 74.6% is explained by other factors outside of the research. done. and the gender diversity of the board of commissioners has an insignificant negative effect on risk management disclosure, leverage and auditor reputation have a significant positive effect on risk management disclosure. The results of the coefficient of determination show a value of 0.254, which means that company size, leverage, board of commissioners size, gender diversity of the board of commissioners, and auditor reputation are able to explain risk management disclosure by 25.4% while the remaining 74.6% is explained by other factors outside of the research. done. and the gender diversity of the board of commissioners has an insignificant negative effect on risk management disclosure, leverage and auditor reputation have a significant positive effect on risk management disclosure. The results of the coefficient of determination show a value of 0.254, which means that company size, leverage, board of commissioners size, gender diversity of the board of commissioners, and auditor reputation are able to explain risk management disclosure by 25.4% while the remaining 74.6% is explained by other factors outside of the research.